To Speed and Expand the Airways... (1944)
Color print advertisement for magnesium alloys manufactured and sold by the Dow Chemical Company. The advertisement features an illustrated depiction of airplane propellers and wings superimposed over a skyline flanked by the an Asian structure with pagoda-style roofs on the left and the British Parliament on the right. The accompanying text details magnesium's lightweight properties relative to aluminum and its potential to increase efficiency in transportation. Notably, the advertisement was produced during World War II and bears the Company's wartime tagline "Dow: Chemicals Indispensable to Industry and Victory."
Keywords: Dow Chemical Company; Chemical industry; Corporations; Advertising; Advertising, Industrial; Magnesium; Magnesium alloys; Magnesium industry and trade; Transportation; World War (1939-1945)